Family Attachment, Self-esteem, Religiosity, Assertiveness, and Sense of Community as Predictors of Adolescent Happiness - Tina Afiatin (ANIMA Indonesian Psychological Journal, 2013)
The level of adolescent happiness can be a predictor for the success of the individual’s next developmental stages. This study aimed to find out the influence of family attachment, self- esteem, religiosity, assertiveness, and sense of community toward adolescent happiness. Hypothesis of the study was: there is an influence of family attachment, self-esteem, religiosity, assertiveness, and sense of community to adolescent happiness. Participants of the study were 791 students of junior high school in four districts of Yogyakarta Province in Indonesia (age = 12-15 years; male = 376, female = 415). Data were collected by distributing Adolescent Happiness Questionnaire, Family Attachment Questionnaire, Self-Esteem Questionnaire, Assertiveness Questionnaire, Religiosity Questionnaire and Sense of Community Questionnaire. Hypothesis was tested using regression analysis. Result showed that family attachment, self- esteem, religiosity, and assertiveness together play significant roles to adolescent happiness (F = 234.23, p < .001, R2 = 54.1%). Tingkat kebahagiaan remaja dapat menjadi prediktor kesuksesan dan kebahagiaan kehidupan individu pada tahap perkembangan selanjutnya. Penelitian ini bertujuan untuk mengetahui pengaruh kelekatan keluarga, harga diri, religiusitas, asertivitas dan rasa kemasyarakatan terhadap kebahagiaan remaja. Hipotesis penelitian :Ada pengaruh kelekatan keluarga, harga diri, religiusitas, asertivitas dan rasa kemasyarakatan terhadap kebahagian remaja. Subjek penelitian adalah 791 siswa Sekolah Menengah Pertama di Daerah Istimewa Yogyakarta, Indonesia, usia 12-15 tahun, terdiri dari laki-laki: 376, perempuan: 415. Pengumpulan data menggunakan Skala Kebahagiaan Remaja, Skala Kelekatan Keluarga, Skala Harga Diri, Skala Religiusitas, Skala Asertivitas, dan Skala Rasa Kemasyarakatan.Uji hipotesis menggunakan teknik Analisis Regresi Ganda. Hasil analisis menunjukkan bahwa kelekatan keluarga, harga diri, religiusitas, dan asertivitas secara bersama-sama memberikan pengaruh secara signifikan terhadap kebahagiaan remaja (F = 234.23, p < .001, R2 = 54.1%)